2017
DOI: 10.3389/fnbeh.2017.00224
|View full text |Cite
|
Sign up to set email alerts
|

Frontal EEG Asymmetry of Mood: A Mini-Review

Abstract: The present mini-review was aimed at exploring the frontal EEG asymmetry of mood. With respect to emotion, interpreted as a discrete affective process, mood is more controllable, more nebulous, and more related to mind/cognition; in addition, causes are less well-defined than those eliciting emotion. Therefore, firstly, the rational for the distinction between emotion and mood was provided. Then, the main frontal EEG asymmetry models were presented, such as the motivational approach/withdrawal, valence/arousal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
63
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(75 citation statements)
references
References 65 publications
(99 reference statements)
6
63
1
1
Order By: Relevance
“…The current study is in line with the observation of Davidson and colleagues 35 and other earlier studies 4,36,63 , where no correlation was observed for affect and BIS/BAS measures with standard hemispheric asymmetry. However, these previous studies never explored the neurovascular underpinnings and associated hemodynamic asymmetry of these underpinnings.…”
Section: Standard Alpha Asymmetry and Its Hli Reveal No Correlation Wsupporting
confidence: 93%
See 1 more Smart Citation
“…The current study is in line with the observation of Davidson and colleagues 35 and other earlier studies 4,36,63 , where no correlation was observed for affect and BIS/BAS measures with standard hemispheric asymmetry. However, these previous studies never explored the neurovascular underpinnings and associated hemodynamic asymmetry of these underpinnings.…”
Section: Standard Alpha Asymmetry and Its Hli Reveal No Correlation Wsupporting
confidence: 93%
“…This linkage was initially observed in many studies where left hemispheric lesion affected the perception of positive emotions whilst damage to the right hemisphere impaired the perception of negative emotions [1][2][3] . Subsequently, there was a surge in elucidating the role of frontal hemispheric asymmetry based on the alpha signature of electroencephalography (EEG) in manifesting the individual differences in affect and approach/withdrawal measures [4][5][6] . Davidson et al [7][8][9] , in their studies, suggested the lateralization of the prefrontal cortex (PFC) with respect to positive/motivational valence.…”
mentioning
confidence: 99%
“…Electroencephalogram (EEG) was used to measure brainwave activity, which has been extensively used in research and clinical practice to evaluate an individual's real-time emotional reactions towards specific stimuli (Palmiero and Piccardi, 2017;Wu and Sun, 2018), particularly that music perception and emotional processing are interweaved, which may lead to EEG power change (Lin et al, 2010). Furthermore, EEG is considered the optimal modality for recording human brainwave activity (Lokannavar et al, 2015).…”
Section: Measurements and Instrumentationmentioning
confidence: 99%
“…Вместе с тем наблюдается усиление высокочастотного бета-ритма в задних сенсомоторных областях неокортекса. Что касается альфа-активности, наблюдается её фронтальная асимметрия [20,25] и гипоактивация левой фронтальной доли, которую при стрессе связывают с повышением риска развития расстройств психики [24]. Авторы работы [19] также предполагают, что при стрессе повышается риск формирования таких психических расстройств, как депрессия, тревожные состояния и др.…”
Section: аффективные психические расстройстваunclassified